Authentic leadership’s effect on customer orientation and turnover intention among Portuguese hospitality employees - Ribeiro, Neuza (2020)
Abstract Purpose Hospitality employees’ attitudes and behaviors play a crucial role in enhancing customer satisfaction and service quality and ultimately firms’ success; therefore, organizations must have skilled, customer-oriented staff. More research is required to help hospitality managers gain insights into the best strategies to promote and retain customer-oriented employees. This study specifically sought to provide a more comprehensive understanding of the ways that authentic leadership (AL) can affect employees’ customer orientation and turnover intention, including exploring affective commitment’s (AC) potential mediating role.